(untitled) (Journal of Engineering, 2006)
Basrah crude oil Vacuum residue 773+ K with specific gravity 1.107 and 4.87wt. % sulfur, was treated with hexane commercial fraction provided from Al-Taji Gas Company for preparing deasphaltened oil(DAO)suitable for hydrotreating process. Deasphaltening was carried out with 1h mixing time, 10ml:1g solvent to oil ratio and at room temperature. Hexane deasphaltened oil was hydrotreated on presulfied commercial Co-Mo/ 2 3 g − Al O catalyst in a trickle bed reactor. The hydrotreating process was carried out at temperature 660 K,LHSV 1.3 h –1, H2/oil ratio 300 l/l and constant pressure of 4MPa. The hydrotreated product was distillated under vacuum distillation unit. It is found that the mixture of 75% of vacuum residue with 25% anthracene satisfies with requirements for graphite electrodes binder.